Hierarchical binding of copperII to N-truncated Aβ4–16 peptide. Issue 4 (1st April 2020) - Teng, Xiangyu; Stefaniak, Ewelina; Girvan, Paul; Kotuniak, Radosław; Płonka, Dawid; Bal, Wojciech; Ying, Liming
Abstract : Multiple intermediates were found in Cu(ii ) binding to Aβ4–16 before the formation of a tight complex. Abstract : N-Truncated Aβ4–42 displays a high binding affinity with Cu II . A mechanistic scheme of the interactions between Aβ4–42 and Cu II has been proposed using a fluorescence approach. The timescales of different conversion steps were determined. This kinetic mechanism indicates the potential synaptic functions of Aβ4–42 during neurotransmission.